Calvino-Desai, On Freedom and Estrangement. Rules and Boundaries of Life on a Tree - Radoš-Perković, Katja (2012)
Both Italo Calvino (The Baron in the Trees) and much later Kiran Desai (Hullabaloo in the Guava Orchard) created an alternative life-space above ground, on the trees. In the case of Calvino's character Cosimo, it is a life-long experience started by a child who matures in this new environment and takes active part in the surrounding important historical events. Desai's Sampath ends on a guava tree almost by accident, in his adult age, and does not control the repercussions of this choice. The paper discusses the similarities and differences between the two different concepts of freedom advocated by the characters, along with the inevitable rules and boundaries attached to these utopias.